2021
DOI: 10.1007/s40692-021-00185-w
|View full text |Cite
|
Sign up to set email alerts
|

Will–skill–tool (WST) model of technology integration in teaching science and mathematics in the Philippines

Abstract: The proliferation of information and communication technologies (ICT) in the twenty-first century has challenged the status quo of educational setting and led to a paradigm shift in teaching and learning processes. ICT use and integration in teaching then, becomes an essential component of pedagogical processes to have an effective teacher–student interaction and to optimize learning. While past studies have already established evidence that attitude toward ICT (will), ICT skills (skill), and availability of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 30 publications
0
9
1
1
Order By: Relevance
“…Nevertheless, it mainly regards the need to learn about the background and use of technologies. The latter finding contrasts with those reported by Sasota and colleagues [22], who found science teachers to score higher on the WST model than mathematics teachers. It might be noted that their research was done among teachers in the Philippines: therefore, this difference might be explained by the different contexts.…”
Section: Discussioncontrasting
confidence: 93%
“…Nevertheless, it mainly regards the need to learn about the background and use of technologies. The latter finding contrasts with those reported by Sasota and colleagues [22], who found science teachers to score higher on the WST model than mathematics teachers. It might be noted that their research was done among teachers in the Philippines: therefore, this difference might be explained by the different contexts.…”
Section: Discussioncontrasting
confidence: 93%
“…The WST model focuses on the proficiency of teachers (Christensen & Knezek, 2016) and postulates that the teachers` beliefs with regard to digital technologies (will), their technical skills (skill), and the digital equipment available for the teacher (tool) are the most important predictors for technology integration (Knezek et al, 2003;Niederhauser & Lindstrom, 2018). This postulation has been confirmed by many studies showing that those three predictors play a very important role in technology integration (Agyei & Voogt, 2011;Petko, 2012;Farjon et al, 2019;Knezek et al, 2003;Knezek et al, 2000;Knezek & Christensen, 2008Morales Velazquez, 2007;Pozas & Letzel, 2021;Sasota et al, 2021;Sawyerr & Agyei, 2022). In the majority of older studies technology integration was measured as the teachers` familiarity, beliefs, and self-efficacy with regard to digital technologies that can be confounded with the will-and skill-component of the WST model (see for example Agyei & Voogt 2011;Knezek et al, 2003;Knezek & Christensen, 2016).…”
Section: Will-skill-tool Model With Regard To Learning Analytics In S...mentioning
confidence: 96%
“…In the majority of older studies technology integration was measured as the teachers` familiarity, beliefs, and self-efficacy with regard to digital technologies that can be confounded with the will-and skill-component of the WST model (see for example Agyei & Voogt 2011;Knezek et al, 2003;Knezek & Christensen, 2016). To avoid this confounding problem other studies have operationalized technology integration as the frequency of technology use by teachers and students in class and have investigated it in combination with key components of the WST model (see Petko, 2012;Schmitz et al, 2022;Sasota et al, 2021;). However, in a European large scale assessment study it was found that will-, skill-and tool-components were only of minor importance for the frequency of technology use (e.g., computer and internet applications) by students and teachers in class (Schmitz et al, 2022).…”
Section: Will-skill-tool Model With Regard To Learning Analytics In S...mentioning
confidence: 99%
“…While categorising the factors affecting education on the basis of subjects, there have been studies related to mathematics and science (Sasota et al. , 2021), English (Alobaid, 2020) to cope up with during the pandemic.…”
Section: Thematic Corementioning
confidence: 99%